Sensitivity assay of semi-nested reverse-transcription polymerase chain reaction in detecting HCV-RNA from chronic renal disease patient - Hamzah, Hairul Aini; Mustafa Mahmoud, Mohammed Imad Al-Deen; Abdullah , Nasuruddin (2011)
Hepatitis C is a never-ending public health problem and the prevalence among chronic renal disease (CRD) patient always exceeds the general population. We studied the sensitivity of semi-nested reverse-transcription polymerase chain reaction (sn RT-PCR) technique for the detection of hepatitis C virus (HCV) infection among patients with chronic renal problem who underwent haemodialysis treatment. An assay was evaluated using a positive control with known HCV viral load (2,148,000 IU/ml), which was determined at Gribbles Laboratory (Australia). A 10-fold serial dilution of the serum sample was conducted prior to RNA extraction and sn RT-PCR. The amplicon band was observed by electrophoresis in 1.7 % gel. Then, fifty-three (53) patients with known no infection to the HCV were collected and further tested with the established assay. The sensitivity result showed that the assay was sensitive enough to detect viral RNA up to 1:10 000 dilution (2.148 IU/ml). Further investigation on the serum samples of the CRD patients revealed four positive cases (7.6 %) which one of them seroconverted to positive. In conclusion, the established assay was highly sensitive in detecting HCV infection among seronegative CRD patient. The assay can be further improved and used as a HCV screening tool.